Microstructure and Tribological Properties of Magnetron Sputtering DLC Film on GCr15 Steel Surface for Pile Driver - WANG Xiao-jing, LI Li-qing (Cailiao Baohu, 2021)
In order to improve the tribological properties of GCr15 steel used in pile driver, a layer of DLC film doped with Cr was prepared on its surface by magnetron sputtering. The microstructure and tribological properties of the film under different working conditions were compared. Results showed that many spherical particles appeared in the surface area of the DLC film, the microstructure of the film was relatively uniform, and the surface roughness was close to 9 nm. The DLC film formed a single diffraction peak, indicating that DLC film belonged to an amorphous structure. The nano-indentation test of DLC film displayed a smooth transition load change curve, and it was inferred that the prepared DLC film was composed of uniform tissues. Furthermore, when NaCl solution was used as lubricating medium, the friction coefficient was 0.079, and a relatively stable curve was obtained, owing to NaCl solution having a good antifriction effect on the contact surface of the friction pair. Compared with the GCr15/GCr15 pair without DLC film, the DLC/GCr15 pair possessed a smaller friction coefficient, indicating that DLC film could have a good anti-friction effect on GCr15 steel. When the contact pressure increased from 1.00 MPa to 3.60 MPa, the friction coefficient decreased. Further increase of contact pressure would be accompanied by the friction heating, which accelerated the graphitization process of DLC film and caused the friction coefficient to increase to a certain extent.